Effects of GRIN2B, GRIA1, and BDNF Polymorphisms on the Therapeutic Action of Ketamine and Esketamine in Treatment-Resistant Depression Patients: Secondary Analysis From a Randomized Clinical Trial. Issue 6 (11th November 2022) - Beanes, Graziele; Caliman-Fontes, Ana Teresa; Souza-Marques, Breno; Silva, Hátilla Dos Santos; Leal, Gustavo C.; Carneiro, Beatriz Alves; Guerreiro-Costa, Lívia N.F.; Figueiredo, Alexandre V.; Figueiredo, Camila Alexandrina V.; Lacerda, Acioly L.T.; Costa, Ryan dos S.; Quarantini, Lucas C.
Abstract : Objective: This study aimed to evaluate the effect of genetic variants in glutamate ionotropic receptor N-methyl-d -aspartate type subunit 2B ( GRIN2B ), glutamate ionotropic receptor α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid type subunit 1 ( GRIA1 ), and brain-derived neurotrophic factor ( BDNF ) genes on therapeutic response, remission, and total Montgomery-Åsberg Depression Rating Scale scores after treatment with ketamine or esketamine in treatment-resistant depression (TRD) patients. Methods: Participants (N = 60) are from a double-blind, randomized, noninferiority clinical trial comparing single-dose intravenous ketamine (0.5 mg/kg) to esketamine (0.25 mg/kg) for TRD. Montgomery-Åsberg Depression Rating Scale was applied at baseline, 24 hours, 72 hours, and 7 days postinfusion to assess depressive symptoms. Blood samples were collected to evaluate single nucleotide polymorphisms rs1805502 ( GRIN2B ), rs1994862 ( GRIA1 ), and rs6265 ( BDNF ). Results: There was no association between rs1805502, rs1994862, or rs6265 polymorphisms and antidepressant response ( P = 0.909, P = 0.776, and P = 0.482, respectively), remission P = 0.790, P = 0.086, and P = 0.669), or Montgomery-Åsberg Depression Rating Scale scores at each time point ( P = 0.907, P = 0.552, and P = 0.778). Conclusions: We found no association between the studied single nucleotide polymorphisms (rs6265, rs1805502, and rs1994862) and ketamine's therapeutic action in TRD patients. Further studies with larger samples are needed to clarify the utility of these genes of interest as predictors for antidepressant treatment.